124. Evaluation of dose calculation accuracy at lung-tissue interface in presence of magnetic field with Gafchromic EBT3. (December 2018) - Cusumano, D.; Teodoli, S.; Greco, F.; Fidanzio, A.; Boldrini, L.; Massaccesi, M.; Cellini, F.; Valentini, V.; De Spirito, M.; Azario, L.
Abstract: Purpose: Aim of this study is to investigate the MRIdian (ViewRay) TPS accuracy in calculating the dose distribution in presence of magnetic field at tissue-lung interface, where the electron return effect (ERE) plays a primary role. Methods: The investigation was realised using Gafchromic EBT3 films. A dose calibration step was planned on MRIdian, exposing thirteen 3 × 3 cm 2 film pieces perpendicularly to the beam axis at different Co-60 source exposure times (15–460 s). Films were arranged in a slab water phantom (SAD = 105 cm; SSD = 100 cm) and analysed one day after irradiation. An absolute dose measurement was performed by using a 125 cc ion chamber to estimate correlation between exposure time and absorbed dose. To evaluate dose accuracy at lung-tissue interface, two EBT3 films were inserted at the interfaces of a non-homogeneous sandwich phantom composed by a 5 cm lung-equivalent slab ( ρ = 0.39 g/cm 3 ) embedded inside two water-equivalent slabs (see Fig. 1). Three treatment plans were calculated and delivered: Plan A: one 4.2 × 4.2 cm 2 beam delivered at 0 degree Plan B: three 6.3 × 6.3 cm 2 beams delivered at 330, 0 and 30 degree Plan C: an IMRT complex plan constituted by 9 equidistant beams The dose distributions measured by EBT3 films were compared to those calculated by TPS in terms of 1%/1 mm, 3%/1 mm, 3%/3 mm and 25 cGy/1 mm gamma analysis. The dosimetric workflow was also validated by delivering Plan A on a totally homogeneous phantom. Results: Table 1 contains the γ < 1 values obtained for the different plans delivered. All plans show a 3%/3 mm gamma-passing rate higher than 90% (tolerance criteria recommended for IMRT by ESTRO Booklet 7). When tighter spatial criteria were considered (delta distance = 1 mm), a decrease of passing rate is observed, whose entity is correlated to the plan complexity. Conclusions: MRIdian TPS is able to calculate with high accuracy dose distribution in presence of magnetic field at the tissue-lung interface, correctly modelling the ERE contribution.